Mice with genetically altered glutamate receptors as models of schizophrenia: a comprehensive review - Inta, Dragos; Monyer, Hannah; Sprengel, Rolf; Meyer-Lindenberg, Andreas; Gass, Peter (Neuroscience & biobehavioral reviews, 2010)
Recent clinical evidence for the effectiveness of new antipsychotic drugs that specifically target glutamate receptors has rekindled interest in the glutamatergic system regarding pathophysiology and treatment of schizophrenia. The glutamatergic hypothesis of schizophrenia was triggered by the clinical/behavioural observation that NMDA receptor antagonists can induce psychosis in humans and abnormal behaviour with schizophrenia-like symptoms in animals. Initial models focused on NMDA receptor hypofunction as a potential pathogenetic mechanism. More recent genetic and pharmacological studies revealed that malfunction of other components of the glutamatergic system might also be relevant in explaining specific symptoms of this complex disease. Here, we review mutant mouse models with relevance for schizophrenia. These rodent models, in which specific glutamate receptor subtypes or various components of their intracellular transduction machinery are genetically altered, permit a detailed dissection of the contribution of different components of the glutamate system in inducing schizophrenia-like behaviours. They may provide insight into the pathophysiology of schizophrenia and prove useful in the development of new therapeutics.
Gesehen am 30.06.2023